2009
DOI: 10.1088/1742-5468/2009/01/p01039
|View full text |Cite
|
Sign up to set email alerts
|

The influence of noise on electron dynamics in semiconductors driven by a periodic electric field

Abstract: Studies about the constructive aspects of noise and fluctuations in different non-linear systems have shown that the addition of external noise to systems with an intrinsic noise may result in a less noisy response. Recently, the possibility to reduce the diffusion noise in semiconductor bulk materials by adding a random fluctuating contribution to the driving static electric field has been tested. The present work extends the previous theories by considering the noise-induced effects on the electron transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…This counterintuitive effect has been found in different physical areas, ranging from the generation of spin currents [29], aggregation kinetics of Brownian particles [30,31], chemical reaction system [32], translocation dynamics of polymers [33][34][35], ultra-fast magnetization dynamics of magnetic spin systems [36,37], dynamic electron response in zinc-blende semiconductor crystals [38][39][40][41][42][43], noise redistribution in quasi 2D Silicon Mos inversion layers [44], to interdisciplinary physical models [45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…This counterintuitive effect has been found in different physical areas, ranging from the generation of spin currents [29], aggregation kinetics of Brownian particles [30,31], chemical reaction system [32], translocation dynamics of polymers [33][34][35], ultra-fast magnetization dynamics of magnetic spin systems [36,37], dynamic electron response in zinc-blende semiconductor crystals [38][39][40][41][42][43], noise redistribution in quasi 2D Silicon Mos inversion layers [44], to interdisciplinary physical models [45][46][47][48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade an increasing interest has been devoted towards possible constructive aspects of noise and fluctuations in physical and biological systems [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Previous studies have shown that, under specific conditions, an external noise can constructivelly interact with an intrinsically nonlinear system, characterized by the presence of intrinsic noise, giving rise to positive effects [13][14][15] such as stochastic resonance (SR) [16][17][18][19], resonant activation (RA) [20,21] and noise enhanced stability (NES) [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that, under specific conditions, an external noise can constructivelly interact with an intrinsically nonlinear system, characterized by the presence of intrinsic noise, giving rise to positive effects [13][14][15] such as stochastic resonance (SR) [16][17][18][19], resonant activation (RA) [20,21] and noise enhanced stability (NES) [22][23][24][25][26]. In particular, the possibility to suppress the intrinsic noise in n-type GaAs and Si bulk, driven by a static electric field, with the addition of a Gaussian correlated noise source, has been theoretically investigated [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations